The Transmission Mechanism of Russian Central Banks Countercyclical Monetary Policy since 2011: Evidence from the Interest Rate Pass-Through - Nguyen, Chu V.; Phan, Khoi Dinh; Williams, Marvin (Journal of Eastern European and Central Asian Research (JEECAR), 2017)
The study is an investigation of the nature of the Russian interest rate pass-through from February 2011 to November 11, 2016. The empirical results reveal a relatively low short-run interest pass-through of 0.662937 and an incomplete long-run interest rate pass-through of 0.826353. The bounds test results indicate no long-term relationship between countercyclical monetary policy and market rates. These empirical findings suggest that the Russian Central Bank has not been very effective in formulating and implementing its countercyclical monetary policy. In light of the formidable political and economic challenges faced by the Russian Federation over this sample period, the results are hardly surprising.